Does False and Missed Lane Departure Warnings Impact Driving Performances Differently?. Issue 14 (27th August 2019) - Navarro, Jordan; Deniel, Jonathan; Yousfi, Elsa; Jallais, Christophe; Bueno, Mercedes; Fort, Alexandra
ABSTRACT: Lane Departure Warning Systems (LDWS) are known to be effective at preventing lane departures. The current study aimed to further investigate the influence of LDWS incorrect warnings along with the warning onset on driving performances. Performances were considered during missed warned lane departure episodes, as well as correctly warned lane departure episodes following incorrectly warned (false or/and missed warning) episodes. In the reported experiment, the incorrect warnings order of presentation was manipulated along with the warning onsets (partial and full lane departure). Results pointed out that a missed warning is impairing driving performances during the missed warned situation, whereas a false warning is impairing driving performances for the subsequent lane departure. Moreover, if false warning impairment is magnified by the occurrence of a subsequent missed warning, this multiplicative effect is restricted to the following lane departure only. These findings bring both theoretical and practical insights. From a theoretical perspective, the human–machine cooperation LDWS model was refined by the adjunction of a transitional influence of incorrect warnings on the information processing. From a practical perspective, the recommendation to avoid false warnings as much as missed warnings was made.